Implications of bleeding in acute coronary syndrome and percutaneous coronary intervention - Pham PT (Vascular Health and Risk Management, 2011)
Phuong-Anh Pham1, Phuong-Thu Pham2, Phuong-Chi Pham3, Jeffrey M Miller4, Phuong-Mai Pham5, Son V Pham61Department of Medicine, Division of Cardiovascular Diseases, VA Medical Center and University of Tennessee Health Science Center, Memphis, TN, USA; 2Department of Medicine, Nephrology Division, Kidney Transplant Program, David Geffen School of Medicine at UCLA; 3Department of Medicine, Nephrology Division, 4Department of Medicine, Hematology-Oncology Division, UCLA-Olive View Medical Center and David Geffen School of Medicine at UCLA; 5Department of Medicine, Greater Los Angeles VA Medical Center and David Geffen School of Medicine at UCLA, Los Angeles, CA, USA; 6Department of Medicine, Division of Cardiovascular Diseases, Bay Pines VA Medical Center, Bay Pines, FL, USAAbstract: The advent of potent antiplatelet and antithrombotic agents over the past decade has resulted in significant improvement in reducing ischemic events in acute coronary syndrome (ACS). However, the use of antiplatelet and antithrombotic combination therapy, often in the settings of percutaneous coronary intervention (PCI), has led to an increase in the risk of bleeding. In patients with non-ST elevation myocardial infarction treated with antithrombotic agents, bleeding has been reported to occur in 0.4%–10% of patients, whereas in patients undergoing PCI, periprocedural bleeding occurs in 2.2%–14% of cases. Until recently, bleeding was considered an intrinsic risk of antithrombotic therapy, and efforts to reduce bleeding have received little attention. There have been increasing data demonstrating that bleeding is associated with adverse outcomes, including myocardial infarction, stroke, and death. Therefore, it is imperative to optimize patient outcomes by adopting pharmacological and nonpharmacological strategies to minimize bleeding while maximizing treatment efficacy. In this paper, we present a review of the bleeding classifications used in large-scale clinical trials in patients with ACS and those undergoing PCI treated with antiplatelets and antithrombotic agents, adverse outcomes, particularly mortality associated with bleeding complications, and suggested predictive risk factors. Potential mechanisms of the association between bleeding and mortality and strategies to reduce bleeding complications are also discussed.Keywords: bleeding risk, antiplatelets, antithrombotics, acute coronary syndrome, percutaneous coronary intervention